Antifungal properties of natural products from Pterocarya tonkinensis against phytopathogenic fungi. Issue 4 (24th December 2020) - Thi Ngo, Men; Han, Jae Woo; Van Nguyen, Minh; Le Dang, Quang; Kim, Hun; Choi, Gyung Ja
Abstract: BACKGROUND: In the search for new natural resources showing antifungal activity, we found that the methanol extract of Pterocarya tonkinensis (Fr.) Dode suppressed the disease development caused by fungi. The objectives of this article were (i) to isolate and identify the antifungal substances from the Pterocarya tonkinensis extract based on a bioassay‐guided fractionation and (ii) to investigate their potential as a biocontrol agent with their antifungal activities in vitro and in vivo . RESULTS: Eighteen compounds were identified from the methanol extract of Pterocarya tonkinensis, including two new natural products 1 and 2 : 1, pterocaryalactone; 2, pterocaryafuranone; 3, (1 S, 6 R )‐9‐hydroxymegastigm‐7‐en‐3‐one; 4, ( S )‐dimethyl malate; 5, α ‐linolenic acid; 6 –8, α ‐tetralones; 9, ( R )‐methyl‐2‐hydroxyl‐3‐phenyl‐propanoate; 10, ( E )‐4‐hydroxycinnamic acid methyl ester; 11 –14, diarylheptanoids, and 15 –18, pentacyclic triterpenoids. Based on the results of the in vitro antifungal assay, Magnaporthe oryzae and Phytophthora infestans were the most sensitive to the isolated compounds among the tested phytopathogenic fungi. When ten active compounds were applied onto plants at a concentration of 100 or 500 μg mL −1, compounds 1 and 8 effectively suppressed rice blast disease, and compounds 15 and 16 not only strongly reduced the development of blast on rice but also effectively controlled the development of late blight on tomatoes. CONCLUSION: This is the first report to evaluate the in vitro and in vivo antifungal activities of the isolated compounds from a methanol extract of Pterocarya tonkinensis against phytopathogenic fungi, and our results suggest that Pterocarya tonkinensis and its substances can be used as a source to develop natural fungicides. © 2020 Society of Chemical Industry Abstract : The methanol extract of Pterocarya tonkinensis showed a promising disease control efficacy against rice blast and tomato late blight. Bioassay‐guided fractionation led to 18 active compounds, including two new compounds identified from a natural resource for the first time. © 2020 Society of Chemical Industry